The Role of Artificial Intelligence in Financial Forecasting: A Systematic Literature Review - Utama, Ahmad Nur Budi; Hidayat, Muhammad (Accounting Studies and Tax Journal (COUNT), 2024)
This research examines the impact of using Artificial Intelligence (AI) in real-time financial forecasting on risk management strategies during the global financial crisis. By using a systematic literature review approach, this research aims to comprehensively evaluate existing literature regarding the application of AI in financial prediction and its impact on risk mitigation. The research process involved collecting data from various academic sources, applying the PRISMA method to ensure the quality and repeatability of the results, and thematic analysis to identify key themes and patterns. The main findings show that AI-enhanced real-time financial forecasting can improve prediction accuracy and speed up responses to financial risks, but it is also faced with challenges such as limited data and the risk of overfitting. This research makes a significant contribution to both academic literature and industry practice by offering guidance for financial institutions in leveraging AI for risk management. Practical implications include investment in technology infrastructure, staff training, and integration of AI with existing risk management systems. It is hoped that this research will enrich understanding of the role of AI in financial forecasting and provide a strong basis for further research in this area.